Analisis Sistem Jadwal Meeting Menggunakan Prototype dan Iso 25010 pada PT Teknologi Informatika Solusindo - Emilia Mulya Saputri; Raya Audriansyah; Chairul Anwar (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
PT Teknologi Informatika Solusindo still faces challenges in managing meeting schedules, including manual recording processes, delays in information dissemination, and the potential for scheduling conflicts. These issues can affect the effectiveness of coordination and communication among employees. This study aims to analyze, design, and evaluate a web-based meeting scheduling system using the Prototype method and the ISO/IEC 25010 standard. Data were collected through observation, interviews, literature review, and documentation. The system was developed using the Prototype method and modeled with Unified Modeling Language (UML), consisting of use case diagrams, activity diagrams, sequence diagrams, and class diagrams. System quality testing was conducted based on ISO/IEC 25010 characteristics to ensure that the developed system meets user requirements. The results indicate that the proposed system is capable of improving meeting schedule management by making it more effective, structured, and accessible. Therefore, the web-based meeting scheduling system can serve as an effective solution to enhance meeting management efficiency at PT Teknologi Informatika Solusindo.